2019
DOI: 10.3390/ijms20194677
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Localization and Its Involvement in the Formation of Concentrated Uranium in the Renal Proximal Tubules of Rats Exposed to Uranyl Acetate

Abstract: Although the kidneys comprise a critical target of uranium exposure, the dynamics of renal uranium distribution have remained obscure. Uranium is considered to function physiologically in the form of uranyl ions that have high affinity for phosphate groups. The present study applied microbeam-based elemental analysis to precisely determine the distribution of phosphorus and uranium in the kidneys of male Wistar rats exposed to uranium. One day after a single subcutaneous injection of uranyl acetate (2 mg/kg), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Uranium colocalization with phosphorus and potassium was observed at the early stages of toxicity, even though uranium compounds precipitate in the cytoplasmic compartment in the form of uranyl phosphate needles after exposure to toxic concentrations (400-2000 μM) of uranium [35][36][37]. The reason for potassium and uranium colocalization cannot be clearly explained, but it has also been confirmed using in vivo systems in uranium-treated rat renal tubules [19]. Protein aggregation due to uranium-protein interaction may also be a reason for detection at the early phase of toxicity because uranyl ions have a high affinity for phosphate groups on biomolecules [38][39][40], even though the formation mechanism is not well understood.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Uranium colocalization with phosphorus and potassium was observed at the early stages of toxicity, even though uranium compounds precipitate in the cytoplasmic compartment in the form of uranyl phosphate needles after exposure to toxic concentrations (400-2000 μM) of uranium [35][36][37]. The reason for potassium and uranium colocalization cannot be clearly explained, but it has also been confirmed using in vivo systems in uranium-treated rat renal tubules [19]. Protein aggregation due to uranium-protein interaction may also be a reason for detection at the early phase of toxicity because uranyl ions have a high affinity for phosphate groups on biomolecules [38][39][40], even though the formation mechanism is not well understood.…”
Section: Discussionmentioning
confidence: 94%
“…Microbeam scanning elemental analysis, which is also known as μ-PIXE (particle-induced X-ray emission with microprobe) analysis, is one of the suitable analytical techniques for detecting the precise distribution of elements in a small specimen with good detection of light elements, such as phosphorus, potassium, and calcium. Our previous studies with animal experiments suggested the colocalization of uranium and the light elements in the renal tubules [19] albeit the positional relationship of these elements in the cell remains unclear. PIXE imaging of S3 cells may provide new insights into the implications of cellular uranium dynamics.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Apoptosis was clearly evident in the bronchiole epithelium in the 56 Mn group at two months. Comparably, Homma et al have reported renal toxicity to uranium exposure in relation to uranium distribution and uranium-induced apoptosis in the kidneys [21][22][23].…”
Section: Discussionmentioning
confidence: 94%
“…In osteosarcoma cells exposed to 300 µM uranyl, precipitates were identified as meta-autunite Ca[(UO2)(PO4)]2(H2O)11 by EXAFS (Pierrefite-Carle et al, 2017). Phosphorous and uranium were colocalized in renal proximal tubules from rats exposed to uranyl acetate as shown by micro-PIXE and micro-EXAFS (Homma-Takeda et al, 2019). In neuron-like cells exposed to 10 µM uranyl we did not observe phosphorous or calcium co-localization with uranium suggesting a different mechanism of aggregation.…”
Section: Multi-elemental Imagingmentioning
confidence: 94%